2016
DOI: 10.1088/1748-605x/12/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluations of a novel post-electrospinning treatment to improve the fibrous structure of chitosan membranes for guided bone regeneration

Abstract: Electrospun chitosan membranes have been investigated for guided bone regeneration but are susceptible to swelling, dissolution, and loss of biomimetic nanofiber structure due to residual acid salts. A novel process was investigated for acidic salt removal from chitosan electrospun in 70% trifluoroacetic acid (TFA) by treating with triethylamine (TEA)/acetone and di-tert-butyl dicarbonate (tBOC) instead of the common NaCO treatment. TFA salt removal and nanofiber structure stabilization were confirmed by EDS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…In addition, similar results of membrane stability and degradation pattern during bone formation over a period of 8 -12 weeks were observed by Shin et al and Su et al where chitosan nanofiber membranes retained its shape and continuity as well as the required space for regeneration[12] [15].In the current study, histologic and micro-CT evaluations confirmed bone formation in calvarial defects as early as 4 weeks. Initially, bony islands were seen below the membranes and thicker osseous tissue was detected at the edges of the defect.…”
supporting
confidence: 90%
“…In addition, similar results of membrane stability and degradation pattern during bone formation over a period of 8 -12 weeks were observed by Shin et al and Su et al where chitosan nanofiber membranes retained its shape and continuity as well as the required space for regeneration[12] [15].In the current study, histologic and micro-CT evaluations confirmed bone formation in calvarial defects as early as 4 weeks. Initially, bony islands were seen below the membranes and thicker osseous tissue was detected at the edges of the defect.…”
supporting
confidence: 90%
“…ESCMs were electrospun using an in‐house box at room temperature and 40–60% humidity 2,19,20 . Chitosan (5.5% w/v) was dissolved in TFA‐DCM (70–30), loaded into 10 ml syringe with 20‐gauge blunt needle, and electrospun at 27 kV onto aluminum foil covered collector plate, rotating at ~8.4 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Combination of natural and synthetic polymers shows some advantages in bone tissue engineering. Some studies indicate positive effect of PCL/chitosan, 44 PCL/collagen, 45 PLA/hydroxyapatite, 46 TEA/tBOC-treated chitosan 47 for bone regeneration. Natural and synthetic polymers has been used to improve some existing solution for bone engineering e.g.…”
Section: Tissue Engineering Selected Applicationmentioning
confidence: 99%